Indirect regeneration of long-term callus cultures in gladiolus: a protocol for stable genetic fidelity - Mousavimatin, Seyedehraziyeh; Mortazavi, Seyed Najmmaddin; Samiei, Leila; Azadi, Pejman (Frontiers in Horticulture, 2025)
Gladiolus is an important and economically valued ornamental plant grown worldwide. One of the major challenges in its micropropagation is maintaining genetic stability during indirect regeneration and long-term callus maintenance. The objective of this study was to develop an optimized indirect shoot regeneration protocol for three commercial Gladiolus cultivars with consistent genetic traits. Callus initiated from the basal part of extended mother corm sprout (EMCS) explants in MS medium supplemented with 2 mgL-1 2,4-D, 2 mgL-1 NAA and 1 mgL-1 BAP. The synthesis of phenolic compounds was effectively controlled by the addition of 150 mgL-1 ascorbic acid, 100 mgL-1 citric acid, and 500 mgL-1 activated charcoal. This medium led to an 80% decrease in the accumulation of phenolic compounds across all cultivars in comparison to the control. For shoot regeneration, calli which were maintained over the long term were transferred to MS medium supplemented with 2 mgL-1 BAP, 2 mgL-1 Kin and 0.25 mgL-1 NAA. This significantly enhanced shoot regeneration percentage (95.55%) and number (39.44 shoots per explant). Additionally, cormel formation was significantly enhanced (16.66 cormels per explant) at the base of regenerated plantlets using MS medium containing 9% sucrose and 2 mgL-1 indole-3-acetic acid, without any cormel formation in the control. Cormels were effectively acclimatized in the greenhouse with 100% survival rate. To demonstrate genetic stability, regenerated plantlets were evaluated by flow cytometry and Inter Simple Sequence Repeat (ISSR) markers, verifying their genetic identification with the mother plants. This study provides a reliable and scalable protocol for the commercial micropropagation of gladiolus, with promising applications in breeding programs that aim at transferring desirable traits such as disease resistance or specific floral features.